Effects of erosion degree, rainfall intensity and slope gradient on runoff and sediment yield for the bare soils from the weathered granite slopes of SE China - Deng, Longzhou; Sun, Tianyu; Fei, Kai; Zhang, Liping; Fan, Xiaojuan; Wu, Yanhong; Ni, Liang (Geomorphology (Amsterdam, Netherlands), 2020)
Soil erosion caused by rainfall is a dominant driving force of ecosystem degradation and has become a worldwide environmental issue. However, few studies have been conducted to investigate the effect of erosion degree on the characteristics of soil erosion. This study aims to investigate the effects of erosion degree, rainfall intensity and slope gradient on erosion processes on bare weathered granite slopes of Southeast China. The method of simulated rainfalls was applied with two soil tanks under three slope gradients (8°, 15°, 25°), four rainfall intensities (60, 90, 120, 150 mm/h) and three erosion degrees (slight (E1), moderate (E2), severe (E3)). The rainfall time lasted 90 min and the paddy samples were collected at every 3 min to determine the runoff rate for surface flow (Rr-s) and interflow (Rr-i), sediment rate (Sr), sediment concentration (Sc) and particle size distribution (PSD). The enrichment ratio (Er) and mean weigh diameter (MWD) of different particles were finally calculated and evaluated. The occurring time of surface flow (Tr-s) and interflow (Tr-i) presented a negative relationship with rainfall intensity and slope gradient, while Tr-s presented an order of E2 > E1 > E3 and Tr-i was negatively related to erosion degree. Rr-s increased with runoff duration and was positively correlated to rainfall intensity and slope gradient but negatively correlated to erosion degree, but Rr-i displayed single-peak curves with runoff duration and was positively related to erosion degree. Sr showed an increasing-deceasing trend with runoff duration and was positively correlated to rainfall intensity and slope gradient. Sr on different slopes displayed an order of E1 > E2 > E3 at the 60 and 90 mm/h rainfalls while it reversed at heavier rainfalls. Sc decreased with runoff duration with light fluctuations. It was found that sediment PSD was corresponding to original soils to a definite extent while MWD and Er were positively correlated to erosion degree. These results facilitate the understandings of runoff and soil erosion processes in the weathered granite regions and erosion degree should be considered in future erosion prediction and modeling. •Characteristics of runoff and sediment on bare weathered granite slopes of SE China•The effects of erosion degree, rainfall intensity and slope gradient were studied.•Sediment PSD corresponded to original soils with more fine-sized particles enriched.•Sediment Er and MWD were positively correlated to erosion degree.•Erosion degree should be considered when conducting erosion prediction and models.